Parent–child communication and timing of interventions are challenges in the Duchenne muscular dystrophy care. (3rd September 2018) - Sætrang, T; Bjørk, I T; Capjon, H; Rasmussen, M
Abstract: Aim: Duchenne muscular dystrophy (DMD) is an X‐linked myopathy affecting one in 3600–6000 live male births. The aim of this study was to gain further insight into how parents experience caring for boys with DMD. Methods: Using a qualitative design, parents in 12 families with boys with DMD, whereof two pairs of siblings, were interviewed in 2014 and 2015. Participants were parents of boys followed at Oslo University Hospital or other hospitals in the south‐eastern health region of Norway. Mean age of the boys was 13 years, range 7–17. Results: Parents expressed the importance of obtaining good information about the diagnosis, supplied with sensitivity for them as clients, and the parents must be involved in timing of interventions. Meeting with others in the same situation was highly appreciated. Many of the parents expressed their own need for support to cope with the difficult situation. Continuity of support in the boys' transition to adulthood was pointed out as important, as well as the need for professional help to talk to the boys about their diagnosis. Conclusion: Our study suggests that professional teams should expand the parental perspective and emphasise a holistic approach in their work with patients with DMD.